Morfologia polinica de especies de la Selva Mediana Subperennifolia en la Cuenca del Rio Candelaria, Campeche - Sanchez Dzib, Y.de los A.=700 1 Sosa Najera, S.; Lozano Garcia, M. del S.
(Es, En)
ilus., 29 ref.
Keywords: PALINOLOGIA; POLEN; ORGANISMOS INDIGENOS; MEXICO; MORFOLOGIA POLINICA; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO